2010
DOI: 10.1002/14651858.cd005535.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Addition of long-acting beta2-agonists to inhaled corticosteroids versus same dose inhaled corticosteroids for chronic asthma in adults and children

Abstract: Background Long-acting inhaled ß2-adrenergic agonists (LABAs) are recommended as ’add-on’ medication to inhaled corticosteroids (ICS) in the maintenance therapy of asthmatic adults and children aged two years and above. Objectives To quantify in asthmatic patients the safety and efficacy of the addition of LABAs to ICS in patients insufficiently controlled on ICS alone. Search methods We identified randomised controlled trials (RCTs) through electronic database searches (the Cochrane Airways Group Speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 279 publications
(230 reference statements)
6
105
0
3
Order By: Relevance
“…Studies have demonstrated that adding the LABA salmeterol to moderate doses of ICS provides greater clinical benefit than increased doses of ICS monotherapy (4,6,7). The combination of Fp/salmeterol (FS) was approved for asthma maintenance therapy in 2000 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that adding the LABA salmeterol to moderate doses of ICS provides greater clinical benefit than increased doses of ICS monotherapy (4,6,7). The combination of Fp/salmeterol (FS) was approved for asthma maintenance therapy in 2000 (8).…”
Section: Introductionmentioning
confidence: 99%
“…9,31,32 Consequently, LABA is only recommended for use in combination with corticosteroids, especially among asthma patients. 3,5,9,18,26,29,31,33 In addition, ongoing concerns about the safety and its use in children has prompted the FDA to require more safety studies from drug companies, including 5 double blinded (DB) randomised controlled trial (RCT) by 2017. 34,35 Within the last few years, studies examined the utilisation of inhaled corticosteroids (ICS)+LABAs (salmeterol and efomoterol) in adult asthma patients and observed no significant increase in cardiovascular AEs, including electrocardiogram (ECG) changes, vital signs, and laboratory variables.…”
Section: Long Acting Beta-2 Agonistsmentioning
confidence: 99%
“…The reported AEs were considered relatively minor in clinical consequences, and showed no difference between the two LABAs. 5,26,37 However, the use of SABAs was permitted in many studies, and it may mask the true effect of LABAs. [38][39][40][41] Some studies also suggested that ICSs can contribute to dose-dependent reduction of cardiotoxicity from LABAs.…”
Section: Long Acting Beta-2 Agonistsmentioning
confidence: 99%
See 2 more Smart Citations